Coordination Behaviour of Mercury(II) Towards Triazine-1-oxides - Sharma, Ramadhar; Thakur, A.K.; Choudhary, S.N.; Sharma, S.N.; Nayan, C.R. (Asian Journal of Chemistry, 2010)
Mercury(II) chelates of monobasic bidentate/tridentate and dibasic tridentate/tetradetate triazene-1-oxides (TH, T´H & T"H2) conform to the stoichiometries (HgT2), (HgT´2) and (HgT"). Four coordinate tetraderal and six coordinate octahedral stereochemistries have been assigned to (HgT2) and (HgT'2) chelates. Highly insoluble (HgT") chelates with apparent coordination numbers three and four have also been obtained. In the case of apparent three coordination the extreme insolubility is due to polymerisation through oxygen instead of oxygen. The quadridentate triazene-1-oxide ligand gives a cage like entrapped mercury (II) chelate. The attainment of six coordination is a consequence of the stereochemical requirements of the ligand donor groups of the ortho-substituents of group. The biocidal activity of triazene-1-oxide ligands and their mercury(II) derivatives has also been screened.